2016
DOI: 10.1371/journal.pone.0153553
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Levels in Undiluted Genital Fluid and Their Relationship to Vaginal pH, Estrogen, and Progesterone

Abstract: BackgroundColonization of the female lower genital tract with Lactobacillus provides protection against STIs and adverse pregnancy outcomes. Growth of genital Lactobacillus is postulated to depend on epithelial cell-produced glycogen. However, the amount of cell-free glycogen in genital fluid available for utilization by Lactobacillus is not known.MethodsEighty-five genital fluid samples from 7 pre-menopausal women taken over 4–6 weeks were obtained using the Instead SoftCup® (EvoFem, Inc., San Diego, CA, USA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 25 publications
3
61
2
Order By: Relevance
“…Several other studies also showed that estrogen contribute to the acidification of the vagina (reviewed in [96]). However, a recent study showed that free glycogen levels, measured in the genital fluids of 7 pre-menopausal women, were negatively associated with pH and progesterone, while estrogen levels had no significant correlation with free glycogen [97].…”
Section: Hormonesmentioning
confidence: 94%
“…Several other studies also showed that estrogen contribute to the acidification of the vagina (reviewed in [96]). However, a recent study showed that free glycogen levels, measured in the genital fluids of 7 pre-menopausal women, were negatively associated with pH and progesterone, while estrogen levels had no significant correlation with free glycogen [97].…”
Section: Hormonesmentioning
confidence: 94%
“…Estrogen production varies throughout the menstrual cycle . High estrogen levels lead to the release of glycogen into the vaginal environment, which is broken down into maltose and glucose by alpha‐amylases present in the vaginal mucosa . Lactobacili residing in the lower genital tract use these carbohydrates in a fermentation process to produce lactic acid, thus lowering the pH of the vagina.…”
Section: The Vaginal Microbiome During Pregnancymentioning
confidence: 99%
“…High estrogen levels lead to the release of glycogen into the vaginal environment, which is broken down into maltose and glucose by alpha‐amylases present in the vaginal mucosa . Lactobacili residing in the lower genital tract use these carbohydrates in a fermentation process to produce lactic acid, thus lowering the pH of the vagina. Lactobacili maintain the vaginal pH between 3.5 and 4.5, thereby creating an unfavorable environment for pathogens According to recent studies, vaginal lactobacilli species also produce antibacterial bacteriocins suggesting an additional protective pathway …”
Section: The Vaginal Microbiome During Pregnancymentioning
confidence: 99%
“…Humans experience continuous, 28-day ovarian cycles between menarche and menopause, governed by fluctuations in reproductive steroids. In humans, estrogen levels are closely linked to lactobacilli abundance and vaginal pH, with an increase in estrogen promoting the thickening of the vaginal epithelium and intracellular production of glycogen (Ayre, 1951; Nauth and Haas, 1985; Patton et al, 2000; but see Mirmonsef et al, 2016). Consequently, lactobacilli are most abundant and vaginal pH is lowest when estrogen levels peak just before ovulation (Drake et al, 1980; Wagner and Ottesen, 1982; Eschenbach et al, 2000).…”
Section: Introductionmentioning
confidence: 99%